English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Find the center and radius for the circle defined by the equation x^2 + y^2 + 4x - 6y + 11 = 0

2007-08-27 06:39:59 · 3 answers · asked by Softball_Super_Star17 3 in Science & Mathematics Mathematics

3 answers

x^2+y^2+4x-6y+11=0
(x+2)^2+(y-3)^2+11-4-9=0
(x+2)^2(y-3)^2=sqrt(2)]^2
It is a circle with center (-2,3) and radius= sqrt(2)=1.4142.

2007-08-27 06:47:04 · answer #1 · answered by Anonymous · 0 0

The equation of the circle is, x^2 + y^2 + 4x - 6y + 11 = 0

now the general equation of circle is, x^2+y^2+2gx+2fy+c=0
and the radius = sq rt of (g^2+f^2-c) & center = (-g,-f)

so, if we compare these two equations we will find ,
2g = 4 or, g = 2 & 2f = -6 or, f = -3

so the center of the given circle will be ( -2 , 3) [ans1]

so the radius of the given circle will be sqrt of ( 2*2 + (-3)(-3) -11) i.e. sqrt of (4 + 9 - 11) i.e. sqrt of 2 i.e. 1.414..... [ans2]

2007-08-27 14:02:22 · answer #2 · answered by sharbadeb 2 · 0 0

Center(-2,3) radius sqrt(4+9-11)=sqrt(2)

2007-08-27 13:48:06 · answer #3 · answered by santmann2002 7 · 0 0

fedest.com, questions and answers